Methodology for experimental studies of aquatic gas hydrates - A E Vorobiev; A B Bolatova; I L Baigalasova (RUDN Journal of Engineering Research, 2012)
Natural gas-hydrates are an unconventional source of energy. Potential reserves of hydrated gas are distributed all over the earth both on the land and offshore. Particular attention was given to the possible methodological support of research of gas hydrates.